A case of cochlear-facial dehiscence revealed after bilateral cochlear implants - Chiara Perazzini; Luce Compagnone; Pascal Chabrot; Luis Boyer; Mathilde Puechmaille; Thierry Mom (Radiology Case Reports, 2024)
The cochlear implant is an implanted auditory prosthesis that can restore severe and profound hearing loss. About 20% of patients with congenital sensorineural hearing loss have a malformation of the inner ear. These abnormalities must be investigated before a cochlear implant because they can lead to intra and postoperative complications and/or anomalies. Most labyrinthine malformations are well known; some are less frequent and can be underdiagnosed at the preoperative computed tomography. This report presents the case of bilateral cochlear-facial dehiscence, bony dehiscence between the facial nerve labyrinthine segment, and cochlear basal turn. In our 56-year-old patient, this malformation was misdiagnosed before the cochlear implant and revealed afterward because of abnormal facial nerve stimulation during intraoperative electrophysiological checking.